Energy Borrowing Transmission Scheme Based on D2D Communication for 5G Networks - Megumi Saito; Takashi Koshimizu; Zhenni Pan; Jiang Liu; Hayato Nakazawa; Shigeru Shimamoto (IEEE Access, 2021)
In our paper, we proposed an Energy Borrowing (EB) transmission scheme which is used to conserve the battery life of user equipment (UE), such as a mobile phone. EB is based on device-to-device (D2D) communication and cellular networks, particularly, on out-band D2D (Wi-Fi Direct, IEEE 802.11) and 5G networks. Since D2D offers higher energy efficiency than cellular networks, in this scheme, a UE with low remaining battery power establishes a D2D connection with a nearby UE, and the nearby UE transfers the low remaining battery UE’s packets to/from gNB (5G-base station). As nearby UE plays an active role in the low remaining battery UE’s connection with gNB. Therefore, we can rephrase that a UE with low battery power is virtually borrowing the battery resources of a nearby UE. This paper introduces the operation protocol and procedure followed by EB with the use of Wi-Fi Direct and 5G networks. Experiments and simulations demonstrate that EB can extend terminal battery lifetime (a valuable characteristic for long-lasting batteries), and it is more effective as compared with the existing scheme that uses only the cellular network.